Exploring the Spatial Spillovers of Digital Finance on Urban Innovation and Its Synergy with Traditional Finance - Song, Xiaoling; Qin, Xuan; Wang, Wanmeng; Li, Rita Yi Man (Ital Publication, 2025)
Research on the driving role of digital finance in urban innovation is scarce. Most existing literature focuses on whether digital or traditional finance contributes more to innovation, ignoring the spatial spillover effect of digital finance and failing to explore whether digital finance complements traditional finance in promoting innovation. Moreover, current studies focus on the provincial dimension but elaborate very little on the implications of BRI node cities. This study fills in the gaps by focusing on the spatial spillover effects of digital finance on urban innovation and complementary functions of traditional finance. It applies the spatial Durbin model to 26 China BRI node cities from 2013 to 2020. The results indicated that digital finance has a significant positive effect on the innovation level of these cities, suggesting that digital and traditional finance systems are complementary in promoting innovation. Moreover, the evidence of spatial spillover proves that innovations in node cities influence neighboring regions. This paper contributes to the interaction between digital finance and urban innovation with new insights. It also fills the literature gap by underlining the spatial dynamics rather than traditional panel approaches. The results are useful for policymakers in harnessing financial mechanisms for innovation and economic growth. Doi: 10.28991/ESJ-2025-09-01-024 Full Text: PDF